Proposing Assessment Methods for Different Learning Outcomes: Project TALOE - Alfredo Soeiro (2016)
It is presented a conceptual model that aligns Learning Outcomes (LO) in Education with assessment strategies based on e-learning. The research problem was made taking into account three areas of research: Assessment, Education and e-Learning. The work managed to verify to what extent e-assessment methods may be used to measure intended Learning Outcomes of Engineering courses. The study was planned to facilitate the curriculum design, the teaching delivery planning, the recognition of e-learning courses and to improve definition of assessment tools. In general terms, the approach chosen was to develop a model that matches various common assessment methods to measure the achievement of the main Learning Outcomes (LO) in the field of engineering. This means that it should be possible for a teacher to define the intended LO of the engineering course and, considering this definition, to write proper and possible adequate assessment methods. The work done in the study proposes a conceptual model ALOA (Aligning Learning Outcomes and Assessment). ALOA was used to describe the Learning Outcomes and the proper assessment and to achieve alignment between these two components of the educational process. The implementation of the model was done defining a web based tool that allows teachers to obtain suggestions for proper assessments in accordance with the type of LO.